The Role of Biopsychosocial Factors in the Onset and Persistence of Hypertension: A Systematic Review - Tahmasbi Abdar , Maryam; Firoozi, Manijeh; Aliramezany Farsangi, Maryam (Health Nexus, 2026)
Hypertension is one of the most common chronic diseases and represents a major clinical and social health concern worldwide. Despite advances in treatment, inadequate control of hypertension remains a major challenge for healthcare systems. Traditional approaches have primarily focused on the biological aspects of the disease; however, recent evidence indicates that psychological and social factors also play a determining role in its development and continuation. The present review aimed to identify and explain the biological, psychological, and social factors contributing to hypertension. This study was conducted based on the principles of systematic review, and 23 eligible articles—identified through searches in major scholarly databases—were examined. Inclusion criteria required studies that directly investigated the role of biological, psychological, or social variables in patients with hypertension. Findings showed that biological factors such as obesity, high body mass index, metabolic disorders, insufficient physical activity, and family history play significant roles in the onset of hypertension. In the psychological domain, stress, anxiety, depression, anger, and difficulties in emotion regulation were associated with elevated blood pressure and reduced treatment adherence. Social factors such as low socioeconomic status, lack of familial or social support, and experiences of violence or discrimination were also identified as significant underlying risk factors. Critical analysis revealed that evidence related to biological factors was generally stronger, while findings related to psychological and social variables—due to cross-sectional designs and predominant use of self-report tools—require further rigorous research. Overall, the review indicates that hypertension is a multidimensional condition and cannot be effectively managed by focusing solely on biological components. Integrating biological, psychological, and social dimensions within the biopsychosocial model can provide a deeper understanding of the condition and support the development of more comprehensive interventions for sustained control and improved quality of life in patients.